Adsorption of Phosphorus Using Cockle Shell Waste - Mohd Zain, Natasya Binti; Md Salleh, Nurul Jannah; Hisamuddin, Nurul Fatihah; Hashim, Shazana; Abdullah, Noorul Hudai (Industrial and Domestic Waste Management, 2022)
This study aims at isolating bacteria capable of producing lysine from decayed banana and pineapple fruits, screening the bacteria for lysine accumulation, and producing lysine in a submerged medium using active isolates. Lysine is one of the potential amino acids not synthesized biologically in the body. It is nutritionally important to man and animals and can be used to supplement food and food materials especially cereal products, to improve protein quality. The banana and pineapple fruits were purchased from 'New market' in Amorji-nike, Enugu State, a total of 10 fruits were used. Some pieces of decayed tissues from the banana and pineapple fruits were transferred by means of sterile techniques, to the nutrient agar contained in covered dishes (Petri-dishes) and incubated at room temperature. The plates were identified by biochemical tests. The bacteria isolated from the decayed banana and pineapple fruits were Pseudomonas species, Corynebacterium species, Staphylococcus aureus, Bacillus species, Escherichia coli, Acetobacter aceti, Erwinia herbicola, and Gluconobacter oxydans. Only two of these bacteria were indicated as lysine producers, and they are Bacillus spp and Acetobacter aceti.